Condições de vida e saúde dos idosos residentes em um município de pequeno porte no sul do Brasil - Dellani, Marcos Paulo (2011)
The phenomenon of population aging has been debated and studied in several countries, aiming to create conditions to attend adequately to the new generation that is growing significantly and quickly. The objective of the research was to identify the elderly life and health conditions in the municipality of Estação RS. The data was collected through a household survey using an adaptation of the Health, Welfare and Aging project tool and the Mini Exam of Mental State for cognitive assessment. It was taken into consideration the dependent variables related to health conditions, functional assessment, cognitive state and the use and access to health services. As independent variables, it was considered the ones listed in the questionnaire Heath, Welfare and Aging and in the Mini Exam of Mental State. It was done a descriptive and inferencial analysis of the data. To investigate the association between the categorical variables, it was applied the Pearson chi-square test and the Fisher exact test. To compare the quantitative variables, it was used the T of Student Tests. The level of significance adopted was 5%. The study included 419 people aged over 60 years old, 57% female. The average age was 69 years old (± 7.6). Attended school 84.3% and 15.7% are illiterate. The place of birth was 78.5% rural. Living with someone 68.3% of the respondents. In the cognitive assessment the elderly showed an average of 28 points (± 4.5), which may indicate preservation in cognitive assessment. 58% of them have very good/good health and 42% regular/bad. A presence of continuous pain for more than three months was reported by 54.6% of the elderly, making it difficult, especially, for walking, sleeping, caring for themselves, damaging the mood, appetite, and or leisure. 25.1% suffered some kind of fall. Out of these, 63.8% fell once and 36.2% had two or more events. The females had a higher incidence of falls, 68.6% (p = 0.005). 74.9% use medication. Regarding to the ability to perform Activites of Daily Living, the bivariate analysis showed an association between sex and the variables such as dressing, caring for themselves, lying down and geting out of bed (p <0.05). By analyzing the ability to perform Instrumental Activites of Daily Living, the main instrumental activities associated with sex, were going up and down stairs, cutting toenails, using public transportation and cleaning the house (p <0.05). When necessary, 70.2% visit a private doctor´s office, 28.6% seek public health and 1% looks elsewhere. When they get sick, 95.7% of the elderly have someone who takes cares of them. The companion, in 50.8% of the cases, is the person responsible for providing this care, in 38.2% of the cases are the sons and daughters. About the caregiver, 53.9% are female, aged over 60 years (47.3%), and the average age is 61 years (± 15.01). These results present to the municipal managers information about the conditions of life and health of the elderly people. Such information points out possibilities of strategic actions in vulnerable points related to this population acess to health, as well as the maintenance and improvement of actions and decisions aiming the qualification of the fundamental attention to the elderly population